Implementation of constructed wetland technology as a nature-based solution for environmental improvement at the upper reach of the Moskva River - Kirill, Shmonin; Korshunova, Natalia; Derevenec, Elizaveta; Volkova, Veronica; Lazareva, Maria; Denisova, Olga; Barbashin, Daniil; Bondar, Zlata; Kharitonov, Sergey (International Journal of Biosciences and Biotechnology; Vol 1 No 1 (2023): Special Issue February (Online First), 2023)
Moskva River is an important freshwater ecosystem for the capital region of Russia but is under the constant anthropogenic influence that, to many extents, harms its water quality. A solution has been proposed to improve the river water quality with constructed wetlands in the suburbs of Moscow. The model settlement was Ilyinsky, with a population of 500 living near the river. Wastewater volume, pollutant concentration, and mass flow rate were calculated. Furthermore, local terrains and Russian legal requirements were considered in formulating the design. Based on current river water conditions, it is necessary to build a vertical flow constructed wetland with an area of at least 3.94 m2 per person. It was also estimated that treatment efficiency and pollutant flow into the river would decrease, which should lead to improved water quality at the monitoring point ’Rublevo’. In addition, the research found other small settlements without access to sewage treatment plants. After data extrapolation, introducing the constructed wetlands will expectedly lead to higher-quality water on the Rublevo section. For instance, TSS will decrease from 20.88 to 5.93 mg/l, Total Nitrogen from 1.71 to 0.21 mg/l, and BOD5 from 211 to its natural value—a similar potential change is observed from NH4 + (currently, 0.07 mg/l) and Total Phosphorus (0.16 mg/l). In conclusion, the implementation of the constructed wetlands in the region can improve water quality